Development of Biology Learning Modules Based on Scientific Literacy to Improve Higher Order Thinking Skills of MA Students on Fungi Material - Siti Aminah; Syarifah Widya Ulfa (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Higher Order Thinking Skills (HOTS) are crucial skills that need to be mastered and cultivated in the 21st-century education. Thus, there is a need for innovative open materials to aid in the development of high-level thinking abilities. This research aims to develop a module based on scientific literacy that is valid, practical, and effective for students. The instruments used include needs analysis through teacher interviews and student questionnaires, validation sheets for media and material experts, and practicality sheets. Additionally, a pre-test post-test sheet is used for effectiveness assessment. Based on the data analysis results, the teaching materials validation received a score of 98.3%, the material validation received a score of 88.3%, the teacher response questionnaire received a score of 92.5%, and the student response questionnaire received a score of 90.4%. The effectiveness assessment yielded an N-Gain score percentage of 71.4%, falling under the high category. Therefore, it can be concluded that the Scientific Literacy-based Module is considered feasible, practical, and effective in facilitating the development of higher order thinking skills.